Growth indicators in orthodontic patients. Part 1: Comparison of cervical vertebral maturation and hand-wrist skeletal maturation - (:unkn) unknown (ARIESDUE SRL, 2010)
Aim The purpose of this study was to predict the skeletal maturation status based on the assessment of cervical vertebrae from lateral cephalometric radiographs and to compare these findings with the skeletal maturity of the same individuals judged from the hand-wrist radiographs. Methods Lateral cephalometric and left hand-wrist radiographs of 393 Caucasian children from 8 to 18 years old were evaluated. On the hand-wrist radiographs the classification of Bjork [1972] and Grave and Brown [1976] was used to assess skeletal maturity (HWSS). Cervical vertebral maturation was also evaluated on lateral cephalometric radiographs using the improved CVMS method described by Baccetti, Franchi, and McNamara [2002]. These methods were correlated using the chi-squared test. Results The chi-square test showed that skeletal maturational values obtained by the CVMS method were significantly correlated with the skeletal values obtained from the hand-wrist analysis for both genders (p<0.05). However, gender differentiation exists in CVMS method regarding the peak of growth spurt. Conclusion The results of this study show that the CVMS method was compatible with a commonly used hand-wrist analysis method. The lateral cephalometric radiograph belonging to the standard set of records would be sufficient to evaluate skeletal maturity
Keywords: Cervical Vertebral Maturation Stage (CVMS); Hand-Wrist Skeletal Stage (HWSS); CHRONOLOGICAL AGE; MANDIBULAR GROWTH; PUBERTAL GROWTH